2020
DOI: 10.1002/ijc.32927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fusion transcripts indicates widespread deregulation of snoRNAs and their host genes in breast cancer

Abstract: Genomic rearrangements in cancer can join the sequences of two separate genes. Studies of such gene fusion events have mainly focused on identification of fusion proteins from the chimeric transcripts. We have previously investigated how fusions instead can affect the expression of intronic microRNA (miRNA) genes that are encoded within fusion gene partners. Here, we extend our analysis to small nucleolar RNAs (snoRNAs) that also are embedded within protein-coding or noncoding host genes. We found that snoRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…We believe that SNORD63 and SNORD96A play crucial role in the tumorigenesis and development of ccRCC, but the underlying molecular mechanisms needs further studies to illuminate. As described above, snoRNAs are stably expressed and measurable in body fluids, empowering them the potential as biomarkers in various cancer types, such as NSCLC [16][17][18][19][20], CRC [21][22][23][24], breast cancer [25][26][27] and prostate cancer [28][29][30]. In current study, we demonstrated that SNORD63 and SNORD96A acted as the non-invasive diagnostic biomarkers for ccRCC even for early stage ccRCC.…”
Section: Discussionsupporting
confidence: 52%
“…We believe that SNORD63 and SNORD96A play crucial role in the tumorigenesis and development of ccRCC, but the underlying molecular mechanisms needs further studies to illuminate. As described above, snoRNAs are stably expressed and measurable in body fluids, empowering them the potential as biomarkers in various cancer types, such as NSCLC [16][17][18][19][20], CRC [21][22][23][24], breast cancer [25][26][27] and prostate cancer [28][29][30]. In current study, we demonstrated that SNORD63 and SNORD96A acted as the non-invasive diagnostic biomarkers for ccRCC even for early stage ccRCC.…”
Section: Discussionsupporting
confidence: 52%
“…3 D). As we have previously reported miRNA and snoRNA host genes to be enriched in fusion events [ 2 , 3 ], we modeled the probability of a gene being part of a validated fusion event against its status as miRNA host, snoRNA host, and gene length in a logistic regression model. Because of the large differences in expression and gene length between protein-coding and non-coding genes, the analysis was limited to genes annotated by GENCODE as protein-coding.…”
Section: Resultsmentioning
confidence: 99%
“…These can encode chimeric proteins or alter the regulation of gene expression through promoter-swapping. We have previously shown that non-coding and out-of-frame fusions can deregulate the expression of intronically encoded small non-coding RNAs including microRNA (miRNA) and small nucleolar RNA (snoRNA) [ 1 3 ]. There are many well-established examples of oncogenic gene fusions and some have been successfully exploited as targets for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Host genes of canonical snoRNAs were removed from the lists of non‐host 5′ partners as they have also been shown to be overrepresented among fusion transcripts. 27 As a background for the overrepresentation analyses we used all expressed genes in the TCGA‐BRCA cohort. All significant gene sets are included in Table S4 .…”
Section: Resultsmentioning
confidence: 99%
“…This is problematic for the statistics of overrepresentation analysis, so we created gene lists of equal length for every tumour subgroup by randomly selecting equally large sets of non‐host 5′ partners. Host genes of canonical snoRNAs were removed from the lists of non‐host 5′ partners as they have also been shown to be overrepresented among fusion transcripts 27 . As a background for the overrepresentation analyses we used all expressed genes in the TCGA‐BRCA cohort.…”
Section: Resultsmentioning
confidence: 99%